Laboratory-Scale Production of Charcoal from Acacia Wood - Tendinus Werenengga; Selyus Rantepulung; Mickael Ruben Kaiway; Joni Joni (G-Tech: Jurnal Teknologi Terapan, 2025)
This study aims to analyze the production of charcoal from acacia wood (Acacia spp.) as a sustainable energy alternative, considering the depletion of fossil fuel reserves and the abundance of acacia biomass in Indonesia. The carbonization process was conducted through slow pyrolysis for 5 hours using a 12-kg gas cylinder reactor with used oil as fuel, and 1.8 kg of acacia wood pieces (5 cm in diameter, 5 cm in length) as raw material. The results showed a charcoal yield of 38.89% (0.7 kg), which is higher than the conventional range of 25–35%. Proximate analysis, based on estimates and supporting literature, indicated a moisture content of approximately 3%, volatile matter of 18%, ash content of 4%, and fixed carbon of 75%, meeting the SNI 01-1683-1989 standard for high-quality charcoal. Stable temperature distribution during the process ensured optimal decomposition of hemicellulose, cellulose, and lignin, producing charcoal with high calorific value and low emissions. These findings confirm the potential of acacia wood as an environmentally friendly charcoal feedstock, with recommendations for further optimization of temperature in the range of 400–600 °C to enhance production efficiency and reduce reliance on unsustainable forest resources.